2001
DOI: 10.1042/0264-6021:3590055
|View full text |Cite
|
Sign up to set email alerts
|

Chloride intracellular channel protein CLIC4 (p64H1) binds directly to brain dynamin I in a complex containing actin, tubulin and 14-3-3 isoforms

Abstract: Mammalian chloride intracellular channel (CLIC) (p64-related) proteins are widely expressed, with an unusual dual localization as both soluble and integral membrane proteins. The molecular basis for their cellular localization and ion channel activity remains unclear. To help in addressing these problems, we identified novel rat brain CLIC4 (p64H1) binding partners by affinity chromatography, mass spectrometric analysis and microsequencing. Brain CLIC4 binds dynamin I, alpha-tubulin, beta-actin, creatine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 54 publications
2
42
0
3
Order By: Relevance
“…Chloride intracellular channel (CLIC) family proteins are able to translocate from the cytoplasm to various cellular membranes. In particular, CLIC4 (found to be more abundant in bovine BCECs with re-induced BBB functions in our 2-DE study) forms a complex with cytoskeletal components such as β-actin, tubulin and dynamin I [33,34]. Although CLIC4 plays a role in endothelial cell tubular morphogenesis, immunostaining with rhodamine-phalloidin did not reveal a close association with actin [35].…”
Section: Msn Actbmentioning
confidence: 64%
“…Chloride intracellular channel (CLIC) family proteins are able to translocate from the cytoplasm to various cellular membranes. In particular, CLIC4 (found to be more abundant in bovine BCECs with re-induced BBB functions in our 2-DE study) forms a complex with cytoskeletal components such as β-actin, tubulin and dynamin I [33,34]. Although CLIC4 plays a role in endothelial cell tubular morphogenesis, immunostaining with rhodamine-phalloidin did not reveal a close association with actin [35].…”
Section: Msn Actbmentioning
confidence: 64%
“…Further studies suggest that there is a direct functional link of dynamin to the actin cytoskeleton, reporting that dynamin is co-localized with actin filaments and directly binds regulatory components of the actin cytoskeleton [46,47]. Suginta et al [48] identified in the rat brain a protein complex associated with the cytoplasmic domain of the chloride intracellular channel CLIC4 (p64H1), which includes dynamin 1, alpha-tubulin, beta-actin, creatine kinase (KCRB) and two 14-3-3 isoforms. It is interesting that all these proteins, except of CLIC4, are included in Table 1, suggesting that interaction of dynamin, cytoskeletal proteins and 14-3-3 proteins might be relevant to hippocampus functions.…”
Section: Discussionmentioning
confidence: 96%
“…CLIC4 (originally called p64H1, Howell et al 1996) may be associated with anion channel activity in organelles that traffic and fuse in the secretory pathway (Duncan et al 1997;Chuang et al 1999;Edwards 1999), and may "spill over" into the plasma membrane on overexpression (Proutski et al 2002). CLIC4 also binds to cytoskeletal proteins (Berryman and Bretscher 2000;Suginta et al 2001) and associates (like some Bcl-family proteins) with inner mitochondrial membranes as a putative proapoptotic anion channel protein (FernandezSalas et al 2002). It is also known to be involved in fibroblast differentiation (Ronnov-Jessen et al 2002).…”
Section: Introductionmentioning
confidence: 97%